2007
DOI: 10.1111/j.1540-8167.2007.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Peri‐AV Nodal Atrial Tachycardia from the Noncoronary Cusp of the Aortic Valve

Abstract: Catheter ablation from within the base of the NCC represents a safe and effective means to eliminate focal AT arising from the peri-AV nodal region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
52
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 23 publications
8
52
0
8
Order By: Relevance
“…The results of our data and previous reports [1][2][3][4][5][6] demonstrate the following findings: (1) When the earliest atrial activation is found at the RA anteroseptum during mapping in the right atrium and when that site is close to the AVN or His-bundle region, the NSV mapping should always be kept in mind; and (2) When the His-bundle deflection is also recorded at that site, the NSV mapping and a comparison of the timing of the local electrograms at the RA anteroseptum with that of the NSV should be performed.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of our data and previous reports [1][2][3][4][5][6] demonstrate the following findings: (1) When the earliest atrial activation is found at the RA anteroseptum during mapping in the right atrium and when that site is close to the AVN or His-bundle region, the NSV mapping should always be kept in mind; and (2) When the His-bundle deflection is also recorded at that site, the NSV mapping and a comparison of the timing of the local electrograms at the RA anteroseptum with that of the NSV should be performed.…”
Section: Discussionsupporting
confidence: 79%
“…[1][2][3][4][5][6] However, indeed, 1 case that resulted in a complete AV block from the RF energy delivery at the NSV was reported. 7 Therefore, the RF ablation at the NSV might carry a risk of impairing the AV conduction, and much attention should be paid to the delivery of the RF energy at that site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] The location of successful ablation targets includes the noncoronary cusp (NCC) in most case series [1][2][3][4][5] and the left coronary cusp (LCC) in a few case reports. 6,7 To date, larger studies that investigate the electrophysiological characteristics and the safety and efficacy of catheter ablation of these ATs are still lacking.…”
mentioning
confidence: 99%